National racial/ethnic and geographic disparities in experiences with health care among adult Medicaid beneficiaries. (9th January 2019) - Martino, Steven C.; Mathews, Megan; Agniel, Denis; Orr, Nate; Wilson‐Frederick, Shondelle; Ng, Judy H.; Ormson, A. Elizabeth; Elliott, Marc N.
Abstract : Objectives: To investigate whether health care experiences of adult Medicaid beneficiaries differ by race/ethnicity and rural/urban status. Data Sources: A total of 270 243 respondents to the 2014‐2015 Nationwide Adult Medicaid Consumer Assessment of Healthcare Providers and Systems Survey. Study Design: Linear regression was used to estimate case mix adjusted differences in patient experience between racial/ethnic minority and non‐Hispanic white Medicaid beneficiaries, and between beneficiaries residing in small urban areas, small towns, and rural areas vs large urban areas. Dependent measures included getting needed care, getting care quickly, doctor communication, and customer service. Principal Findings: Compared with white beneficiaries, American Indian/Alaska Native (AIAN) and Asian/Pacific Islander (API) beneficiaries reported worse experiences, while black beneficiaries reported better experiences. Deficits for AIAN beneficiaries were 6‐8 points on a 0‐100 scale; deficits for API beneficiaries were 13‐22 points ( P 's < 0.001); advantages for black beneficiaries were 3‐5 points ( P 's < 0.001). Hispanic white differences were mixed. Beneficiaries in small urban areas, small towns, and isolated rural areas reported significantly better experiences (2‐3 points) than beneficiaries in large urban areas ( P 's < 0.05), particularly regarding access to care. Racial/ethnic differences typically did not vary by geography. Conclusions: Improving experiences for racial/ethnic minorities and individuals living in large urban areas should be high priorities for policy makers exploring approaches to improve the value and delivery of care to Medicaid beneficiaries.